Quality of Communication skills of nurses worked at the Hospitals Affiliated to Jahrom University of Medical Sciences, Iran (Bangladesh Journal of Medical Science, 2018)
Objective: Communicating with patients is not only among the principles of care, but it is considered as one of the key roles of nurses. As nurses are skilled in other clinical skills, their communication skills should also be adequate. The aim of this study is to determine nurses’ communication skills.Materials and Methods: This descriptive study was conducted in 2015 in hospitals affiliated to Jahrom University of Medical Sciences. 215 nurses participated in the study using census method. Data was collected using valid and reliable communication skills (α=0.885). The quality of communication skills was classified on three levels: poor, average, and good.Results: Quality of communication skills of 120 (55.8%) of nurses was weak, 95 (44.2%) moderate, and there was no good evaluation (0%). The communication skills of most nurses were weak in the areas of conscious start (75.8%), verbal and nonverbal communication skills (86.5%), inner and outer harmony (92.6%), respect for the patient (94.4%) and the unconditional acceptance of patient (100%). There was a significant relationship between the nurses’ educational level, mean age and work experience with quality of communication skills (p